Friendship in social networks: Aristotelian analysis in a pospandemic context - Sánchez Pérez, Yaiza; Caro , Carmen (Revista Internacional de Teoría e Investigación Educativa, 2025)
According to Aristotle, friendship is necessary for a person to develop to their full potential. However, social networks have brought about a substantial change in the relationships between adolescents. This article aims to reflect on the development of friendship in adolescents in social networks, considering the proposals made by the Stagirite and the situation caused by COVID-19. Thus, the main concepts linked to friendship from the Aristotelian perspective are presented and the transformations they have undergone because of the emergence of social networks are analysed. Among the conclusions, it is stated that the Aristotelian perspective cannot be considered anachronistic but is fundamental for understanding contemporary educational reality. It is committed to underlining the importance of establishing friendships based on character, cultivating those virtues that will favor the development of the person in that environment.